New Electromagnetic Fluids Inextensible Flows of Spacelike Particles and some Wave Solutions in Minkowski Space-time - Korpinar, Zeliha S.; Tuz, Munevver; Korpinar, Talat (Springer/Plenum Publishers, 2016)
In this paper, we construct a new method for inextensible flows of spacelike curves in Minkowski space-time. Using the Frenet frame of the given curve, we present partial differential equations and we obtain solitions some of this equations. We give some characterizations for curvatures of a spacelike curve in Minkowski space-time.
Keywords: Fluid flow; Minkowski space-time; Particles; Solutions